2002
DOI: 10.1080/09658210143000308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of divided attention and word concreteness on correct recall and false memory reports

Abstract: Lists of thematically related words were presented to participants with or without a concurrent task. In Experiments 1 and 2, respectively, English or Spanish word lists were either low or high in concreteness (concrete vs abstract words) and were presented, respectively, auditorily or visually for study. The addition of a concurrent visual or auditory task, respectively, substantially reduced correct recall and doubled the frequency of false memory reports (nonstudied critical or theme words). Divided attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
56
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 49 publications
11
56
1
4
Order By: Relevance
“…Thus, for the present study, values for familiarity and meaningfulness of the 12 critical items were obtained, since they were the two dimensions that contributed most to false recall and recognition in Brainerd et al (2008); additionally, their concreteness and imagery values were obtained, because they have been shown to be related to variability in true recall (which could indirectly affect false memories) by Brainerd et al (2008) and to variability in false memories by Pérez-Mata, Read, and Diges (2002). The analyses showed that the critical words on the highand low-identifialbility lists did not significantly differ in any of these variables (only in the case of concreteness did the difference approach statistical significance).…”
Section: Methodsmentioning
confidence: 84%
“…Thus, for the present study, values for familiarity and meaningfulness of the 12 critical items were obtained, since they were the two dimensions that contributed most to false recall and recognition in Brainerd et al (2008); additionally, their concreteness and imagery values were obtained, because they have been shown to be related to variability in true recall (which could indirectly affect false memories) by Brainerd et al (2008) and to variability in false memories by Pérez-Mata, Read, and Diges (2002). The analyses showed that the critical words on the highand low-identifialbility lists did not significantly differ in any of these variables (only in the case of concreteness did the difference approach statistical significance).…”
Section: Methodsmentioning
confidence: 84%
“…The idea that divided attention at encoding leads to impaired true memory has been well documented (e.g., Baddeley, Lewis, Eldridge, & Thomson, 1984;Craik, Govoni, Naveh-Benjamin, & Anderson, 1996), although the effects of divided attention on false memories has been much less consistent (cf. Dodd & MacLeod, 2004;Perez-Mata, Read, & Diges, 2002). In Experiment 2, we explored how different types of encoding operations influence the value-based false memory effects.…”
Section: Value Effectsmentioning
confidence: 99%
“…For false memories, dividing attention has different effects on false recall than on false recognition. In particular, it has been shown that the introduction of a secondary task at encoding increases false recall (Dewhurst, Barry, & Holmes, 2005;Pérez-Mata, Read, & Diges, 2002;Peters, Jelicic, Gorski, Sijstermans, Giesbrecht, Merckelbach, 2008) but decreases false recognition (Dewhurst, et al, 2005;Dewhurst, Barry, Swannell, Holmes, & Bathurst, 2007). Similarly, when introducing an additional memory load at encoding rather than using a divided attention paradigm, false recognition is reduced (but only in a between-participants condition not in a within-participant design) (Seamon, et al, 1998).…”
Section: Divided Attentionmentioning
confidence: 99%